2015
DOI: 10.1093/mnras/stv2182
|View full text |Cite
|
Sign up to set email alerts
|

Positive correlation between the cyclotron line energy and luminosity in sub-critical X-ray pulsars: Doppler effect in the accretion channel

Abstract: Cyclotron resonance scattering features observed in the spectra of some X-ray pulsars show significant changes of the line centroid energy with the pulsar luminosity. Whereas for bright sources above the so called critical luminosity these variations are established to be connected with the appearance of the high accretion column above the neutron star surface, at low, sub-critical luminosities the nature of the variations (but with the opposite sign) has not been discussed widely. We argue here that the cyclo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 46 publications
5
68
1
Order By: Relevance
“…This is very different from the INTEGRAL spectra at higher luminosities of 2.2×10 37 and 0.2×10 37 erg s −1 (upper two sets of data points in Fig. 1, Mushtukov et al 2015b), which can be well fitted with the standard XRP power-law model modified by a high energy cutoff and a cyclotron absorption line at ∼ 60 and ∼ 50 keV, respectively.…”
Section: Data Analysis and Resultscontrasting
confidence: 58%
See 1 more Smart Citation
“…This is very different from the INTEGRAL spectra at higher luminosities of 2.2×10 37 and 0.2×10 37 erg s −1 (upper two sets of data points in Fig. 1, Mushtukov et al 2015b), which can be well fitted with the standard XRP power-law model modified by a high energy cutoff and a cyclotron absorption line at ∼ 60 and ∼ 50 keV, respectively.…”
Section: Data Analysis and Resultscontrasting
confidence: 58%
“…Moreover, such a large decrease appears to be unrealistic in the context of the two models proposed so far to explain the observed correlation of line energy with flux. In the model by Mushtukov et al (2015b), the observed correlation is produced by the Doppler effect in the flow, whose velocity is affected by radiation pressure, which is more efficient at higher luminosities. The maximal relative shift here is limited by a factor of two, as the flow velocity changes from the free-fall with v ≈ 0.5c to zero.…”
Section: Cyclotron Linementioning
confidence: 99%
“…The energy of the CRSF depends on the accretion rate in good agreement with theoretical predictions: a fit of the data using as best fit model Equation 2 yields E⋆ = 29.56 ± 0.05, with χ 2 = 1.8, assuming a harmonic ratio of 2 (solid line in the top panel of Fig 3). Mushtukov et al (2015) have proposed an alternative theory to explain the positive correlation between CRSF energy and luminosity in subcritical sources: the bulk of the radiation, emitted by the hotspot on the polar cap, travels upwards through the accretion channel interacting with the infalling matter and producing the CRSF at the resonant energies. The line appears redshifted by Doppler effect to the observer due to the velocity profile of the plasma falling towards the NS surface.…”
Section: Discussionmentioning
confidence: 99%
“…Note that an alternative explanation of the positive correlations between Ecyc − Fx and W − Fx at moderate Xray luminosities was recently proposed by Mushtukov et al (2015b). However, that model predicts the opposite sign of the second derivative in the Ecyc − Fx and W − Fx relations (cf.…”
Section: Fitting the Variance-weighted Datamentioning
confidence: 93%